Detection and genomic characterization of coronaviruses among migratory birds in Guangdong Province, China - Yingjie Lian; Ying Huang; Lixia Xie; Quan Liu; Zhengkai Wei; Runfeng Shi; Xinhong Pan; Wenfen Zhang; Jun Ma; Juntao Li (BMC, 2024)
Abstract The recent Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic highlights the significant threat coronaviruses (CoVs) pose to public health. With their extensive cross-continental movements, migratory birds have the potential to serve as reservoirs and vectors for CoVs. This study aimed to investigate the prevalence of CoVs in birds in densely populated areas of Guangdong Province, China. Of the 128 samples collected from birds, six tested positive for CoVs (4.7%, 95% CI: 1.7-9.9%), and three complete viral genomes were obtained through viral metagenomics and PCR. Phylogenetic analysis revealed that two CoVs (MD_XN18 and SG_DWY40) belonged to the Gammacoronavirus genus, while one (CP_XN11) belonged to the Deltacoronavirus genus. Homology analysis revealed that the MD_XN18 strain discovered in mallards shares 95.6-97.4% sequence similarity with chicken infectious bronchitis viruses (IBVs), providing direct evidence that migratory mallards can transmit avian IBVs. Recombination analysis suggested that two genomic regions of SG_DWY40 could originate from unknown sources through recombination, potentially leading to the expression of a novel viral protein, provisionally named NS3.5. These findings underscore the ongoing transmission and evolution of CoVs among birds in cities near Guangdong Province, emphasizing the need for continued monitoring and research.